2018
DOI: 10.3390/nu10101388
|View full text |Cite
|
Sign up to set email alerts
|

The Consumption of Beef Burgers Prepared with Wine Grape Pomace Flour Improves Fasting Glucose, Plasma Antioxidant Levels, and Oxidative Damage Markers in Humans: A Controlled Trial

Abstract: Wine grape pomace flour (WGPF) is a fruit byproduct that is high in fiber and antioxidants. We tested whether WGPF consumption could affect blood biochemical parameters, including oxidative stress biomarkers. In a three-month intervention study, 27 male volunteers, each with some components of metabolic syndrome, consumed a beef burger supplemented with 7% WGPF containing 3.5% of fiber and 1.2 mg gallic equivalents (GE)/g of polyphenols (WGPF-burger), daily, during the first month. The volunteers consumed no b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 54 publications
1
18
1
Order By: Relevance
“…However, more studies are needed to establish if these RWGP-associated positive outcomes in mice can be translated into the human context. However, these results—in addition to our previous published data [18,19,57]—are encouraging on the potential benefits of incorporating wine grape pomace into a regular diet in order to improve cardiovascular health and decrease ASCVD.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, more studies are needed to establish if these RWGP-associated positive outcomes in mice can be translated into the human context. However, these results—in addition to our previous published data [18,19,57]—are encouraging on the potential benefits of incorporating wine grape pomace into a regular diet in order to improve cardiovascular health and decrease ASCVD.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, we have reported that daily consumption of RWGP by patients with at least one component of metabolic syndrome, along with their regular diet, significantly improved blood pressure, glycaemia, and postprandial insulin levels together with an overall improvement of antioxidant defense [18]. Similarly, intake of beef burgers prepared with RWGP showed better fasting glucose, reduced insulin resistance, and improved plasma antioxidant levels and oxidative damage markers in male volunteers with metabolic syndrome [57]. In addition, intake of a drink prepared from red grape pomace can deliver significant amounts of different phenolic metabolites in humans improving insulin sensibility [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…[12,16] The discrepancy could come from the differences in study participants, study design, the beverage type (red or white wine) and approaches to measurement of insulin sensitivity. [15,21,22]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as stated by Urquiaga, Troncoso, Mackenna, Urzua, Perez, Dicenta, de la Cerda, Amigo, Carreno, Echeverria, and Rigotti [23], vegetable waste such as grape pomace contains a variety of bioactive potential antidiabetic constituents such as dietary fiber, phenolic acids, and flavonoids. This makes it difficult to understand the precise mechanisms of action, as the experiments' results might be the response of a synergistic effect of the bioactive components.…”
Section: Anti-obesity and Anti-diabeticmentioning
confidence: 96%
“…Another study using pomace as a functional ingredient was published by Urquiaga, Troncoso, Mackenna, Urzua, Perez, Dicenta, de la Cerda, Amigo, Carreno, Echeverria, and Rigotti [23]. They incorporated wine grape pomace to beef burgers in an attempt to improve antioxidant and metabolic syndrome parameters.…”
Section: Anti-obesity and Anti-diabeticmentioning
confidence: 99%